Pelatihan Koreografi Bagi Warga Kampung Budaya Palawijen untuk Meningkatkan Daya Tarik Wisata - Robby Hidajat; Pujiyanto Pujiyanto; Hartono Hartono; Muhammad 'Afaf Hasyimy; Sri Wulandari (Ilin Institute, 2021)
The purpose of this PkM is to provide tourism choreography training to realize local cultural branding in increasing tourist attraction. The activity is designed considering that so far there are no tourist attractions to welcome visiting guests, especially on special events. The method used in the form of choreography training is a special script in the form of a procession entitled Anoman Gandrung. This play is a development of the Panji play which is generally performed in Malang mask puppets. As a result of training and mentoring for 3 months, KBP residents were able to present an attraction entitled Sesekaran Wayang Topeng through Virtual Culture Tourism.